1965
DOI: 10.1063/1.1697078
|View full text |Cite
|
Sign up to set email alerts
|

Raman Intensities of HDO and Structure in Liquid Water

Abstract: Photoelectric Raman spectra of HDO in 5-mole % isotopically substituted water show single, broad, slightly asymmetric bands in both of the regions containing the uncoupled fundamental stretching motions. An empirical correlation between O–H or O—D stretching frequency and O···O hydrogen-bonded distance has been used to map the frequency coordinate of the spectra onto an intermolecular distance scale, and the Raman bands are replotted on this abscissa. The resulting intermolecular distribution functions for liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(58 citation statements)
references
References 29 publications
4
54
0
Order By: Relevance
“…This interpretation is in agreement with a mixture model describing water as being composed of a limited number of water species (different ring structures or cluster types) that coexist in a temperature-and pressuredependent equilibrium [17]. On the other hand, the alternative continuum model implies that hydrogen bonds are equally distributed in the water sample, and that there is a continuous weakening of the hydrogen bonds with increasing temperature [18]. The presence of nearly-isosbestic points in the infrared spectra of water at different temperatures has usually been taken as support of the mixture model.…”
Section: Appendix More Detailed Interpretation Of the Water Temperatusupporting
confidence: 71%
“…This interpretation is in agreement with a mixture model describing water as being composed of a limited number of water species (different ring structures or cluster types) that coexist in a temperature-and pressuredependent equilibrium [17]. On the other hand, the alternative continuum model implies that hydrogen bonds are equally distributed in the water sample, and that there is a continuous weakening of the hydrogen bonds with increasing temperature [18]. The presence of nearly-isosbestic points in the infrared spectra of water at different temperatures has usually been taken as support of the mixture model.…”
Section: Appendix More Detailed Interpretation Of the Water Temperatusupporting
confidence: 71%
“…Vibrational (infrared and Raman) spectroscopy is a useful technique for study of the effects of the local environment since the O-H stretching vibrations are correlated to the overall structure of water [20][21][22][23][24][25]. Water molecules in bulk water as well as in interacting water can display various hydrogen bonding interactions and orientations [26] that can result in several coordination types of water molecules (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of water with Pluronic macromolecules is viewed as a sum of the interactions of water with individual subunits (EO or PO), each subunit is considered separately and its hydration is viewed as a small solute hydration [1]. It is also proposed that conceptions based on the mixture models are more appropriate than continuous models for description of water interacting with or bound to polymer [21][22][23][24][25]. Our results do not indicate whether mixture or continuous models are more suitable for the liquid state of pure bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…Bernal and Fowler (Bernal & Fowler, 1933) suggested that molecules in liquid water are arranged in a tetrahedral manner, with each water molecule forming approximately four Hbonds with its nearest neighbors. Wall and Horing (Wall & Hornig, 1965) observed the Raman-scattering motions of the HDO molecules in H 2 O or D 2 O and concluded that liquid water does not have any significant fraction of unbonded molecules. Narten and Levy (Narten & Levy, 1969) supported the viewpoint that water molecules in liquid state are arranged in a predominantly tetrahedral geometry based on the observation that the mean separation between nearest neighbor molecules in ice and water are only marginally different.…”
Section: Structure Of Bulk Watermentioning
confidence: 99%